(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Introduction. The changes of the ocular fundus state in alcoholic toxic neuro-retinopathy (ATN) correspond to the stages of the optic nerve edema (Zhaboyedov G. D., 1992): hyperemia, swelling, ischemia and glial atrophy. Purpose. To study the dynamics of the fundus state of patients at different stages of ATN under the influence of detoxification therapy using polyoxidonium. Material and methods. The biomicroophthalmoscopy of 158 patients with ATN was conducted before treatment, after treatment and in 1 month after treatment. Group 1 — conventional treatment, group 2 received Polyoxidonium in addition. Results. In group 1 deterioration of fundus in 1 month after treatment was observed: recurrence of macular edema (ME) in 31,82 % cases at the stage of swelling, the appearance of macula degeneration at the stage of dystrophy with doppler signs of arterio-venous shunt in the superior orbital vein. In group 2 at the stage of swelling more rapid resorption of macula hemorrhages and more often complete disappearance of ME were observed; at the stage of dystrophy there was ME regression, which was not observed in group 1; the deterioration of the fundus in 1 month after treatment was not observed. Conclusions. The complex detoxification therapy using polyoxidonium resulted in the increase in effectiveness of treatment according to the state of the fundus at the stages of swelling and dystrophy of ATN.